Research Trend on Social Banking - Puspita, Amelia Tri; Marlina, Lina (Accounting and Sustainability, 2023)
The implementation of corporate social responsibility is not only for industrial companies that produce negative impacts on the environment and society, but also other sectors such as: services, insurance, communications, bank and non-bank financial institutions. Banks and other financial service providers play an important role as they are not only recipients but also providers of socially responsible investments. Banks can benefit by applying various basic ideas related to CSR to their policies related to human resources and community involvement. This study aims to determine the development map and trends of Social Banking published by reputable journals in the field of Economics and finance. The data analyzed were more than 1744 publications of Scopus indexed research publications. The export data was then processed and analyzed using the R Biblioshiny application program to determine the bibliometric map of the development of the role of Social Banking. The results showed that the number of publications on the development of the role of economic and financial research continues to increase.